Expert system to predict the numbers of livestock in Thi-Qar province - Ali, Shaker K.; Yaseen, Atyaf J.; Mahdi, Amer Y. (University of Thi-Qar Journal, 2019)
Predict the numbers of livestock is one of interesting research area cause the important of livestock in each countries economics, in this paper we design an expert system for predict the numbers of livestock (Sheep, Goat, Cow, Buffalo and Camel) in Thi-Qar province, and we collect the knowledge from (Directorate of meteorological in Nasiriyah, the Veterinary Hospital in Nasiriyah and Directorate of Agriculture in the province of Thi-Qar) and collect the last 5 years to compare the result from our system with actual results by compare year by year in actual world by the same years in our system , There are 10 knowledge which build rules , There are differences numbers of rule for each livestock kinds, there are 813 fuzzy rules for sheep, 558 fuzzy rules for goat, 435 fuzzy rules for cow, 425 fuzzy rules for buffalo and 537 fuzzy rules for camel. There is commands knowledge and there is specified knowledge for each livestock (Sheep, Goat, Cow, Buffalo and Camel), there rules build by using Mamdani fuzzy logic and we use SQL server 2008 to insert these fuzzy rules. The results which we obtained from our fuzzy expert system was gave high accuracy and perfect result.